Topical 5% 5-fluorouracil in the treatment of multifocal basal cell carcinoma of the face: A novel chemotherapeutic approach. (1st November 2016) - Naik, Mayuresh P.; Mehta, Anuj; Abrol, Sangeeta; Kumar, Sandeep; Gupta, Vishnu S.
ABSTRACT: To determine the safety and efficacy of topical 5-fluorouracil (5-FU) 5% ointment in treatment of non-syndromic multifocal basal cell carcinoma. A 55-year-old male patient, with 8 hours of daily sun exposure, having histologically proven and radiologically non-syndromic, multifocal basal cell carcinoma with involvement of 6 sites on the face, was treated with topical 5-FU 5% ointment twice daily over all sites except the site involving lid margin to prevent corneal toxicity. Left lid lesion underwent wide surgical excision with 5-mm clear margins and reconstruction with nasal septal mucoperichondrium and local skin mobilization. Pharmacologic effects first appeared at 4 weeks and by 8 weeks, the lesions had scabbed and had fallen off with no induration but residual mild perilesional erythema. Patient had post-op histopathological clear margins and recovered uneventfully. No recurrence in 6 months. A topical 5-FU 5% ointment represents a paradigm shift in the treatment of BCC from invasive and disfiguring options (surgery and chemoradiotherapy) to cheap, convenient, effective, non-invasive, non-disfiguring topical chemotherapy. Topical 5% 5-FU is a safe and effective modality of treatment of superficial spreading multifocal basal carcinoma, especially lesions larger than 10 mm, where margins cannot be identified clearly and recurrent lesions.